Model experiments on lip, tongue and larynx positions for palatal vowels - Wood, Sidney (Annual Report of the Institute of Phonetics University of Copenhagen, 1978)
Languages contrasting [y] and [i] prefer prepalatal constrictions. The larynx is low for [y] and high for [i], the lips are less rounded for [y] than for [u] and the tongue blade tends to be raised for [y]. The consequences of these manoeuvres were studied in a series of model experiments. Their advantages are twofold: they provide the best plain-flat [i]-[y] spectral contrast and they ensure stable resonance conditions in the vocal tract.